Serjeant Musgrave's Dance and the Politics of Possibility in Two Television Adaptations. Issue 3 (1st January 2014) - Wyver, John
Abstract: John Arden's stage play Serjeant Musgrave's Dance was adapted for British television in a Granada Television production in 1961 and four years later in a three-part BBC Schools version. Although received at its stage premiere in 1959 with puzzlement the play has since been acknowledged as a key work of modern political drama in Britain with its bold use of anti-naturalistic techniques including heightened prose and the integration of ballads. This article explores the politics of the play and considers the ways in which these were retained or removed by the two processes of adaptation for television.